2015
DOI: 10.1038/ijo.2015.216
|View full text |Cite
|
Sign up to set email alerts
|

The central nervous norepinephrine network links a diminished sense of emotional well-being to an increased body weight

Abstract: OBJECTIVES The neurobiological mechanisms linking obesity to emotional distress remain largely undiscovered. METHODS In this pilot study, we combined positron emission tomography, using the norepinephrine transporter (NET) tracer [11C]-O-methylreboxetine, with functional connectivity magnetic resonance imaging, the Beck depression inventory (BDI), and the impact of weight on quality of life-Lite questionnaire (IWQOL–Lite), to investigate the role of norepinephrine in the severity of depression (BDI), as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…We did not replicate the recent finding of decreased thalamic NET availability in obesity, yet, this study sample has not been further characterized in terms of eating behavior. By investigating EE and NET availability in obesity, our study extends recent research in this field …”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…We did not replicate the recent finding of decreased thalamic NET availability in obesity, yet, this study sample has not been further characterized in terms of eating behavior. By investigating EE and NET availability in obesity, our study extends recent research in this field …”
Section: Discussionsupporting
confidence: 74%
“…By investigating EE and NET availability in obesity, our study extends recent research in this field. 7,8 We demonstrated that a higher degree of EE in obese participants is accompanied by a decreased LC NET availability. The LC-NE system is known to be involved in responses to stress.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This observational finding should be discussed with other parameters of neural connectivity in the near future to obtain specific group characteristics. Further work on our sample in parallel with these data included associative analyses with resting-state functional MRI data and neuropsychological measures showing initial findings of NAT-based interaction of neuronal and behavioural activity [27]. Within this further data processing we showed that an increased BMI is related to a lowered NAT availability in the hypothalamus together with changes in a network mediating emotional well-being.…”
Section: Discussionmentioning
confidence: 82%
“…Future studies employing a larger sample size might reveal important individual differences or the influence of gender, stress and genotypes that have been linked to important aspects of eating behaviours and obesity. This is particularly important in light of recent studies on the brain monoaminergic transporter system that also did not show an association between BMI and transporter binding potential across the entire sample [27, 30]. …”
Section: Discussionmentioning
confidence: 99%